Application of the gold ring bundles for innovative non-redundant sonar systems - Riznyk, V.; Bandyrska, O.; Skrybaylo-Leskiv, D. (Archives of Acoustics, 2006)
The paper involves techniques for configure linear, planar or three-dimensional spacetapered arrays of radar or sonar system, using novel designs based on the Perfect Combinatorial Sequencing Theory, namely the concept of Gold Ring Bundles (GRB)s for finding the optimal placement of array antenna elements in the system with respect to minimizing side lobes, while maintaining or improving on resolving ability and the other significant operating characteristics of the system. It is shown that the method provides many opportunities of the concept for configure of non-uniform array with non-redundant aperture of array systems, including acoustics and hydroacoustics.